Low and Ultra-Low Temperature District Heating Equipped by Heat Pumps—An Analysis of the Best Operative Conditions for a Swiss Case Study - Riccardo Toffanin; Paola Caputo; Marco Belliardi; Vinicio Curti (Energies, 2022)
The manuscript analyses the management of low and ultra-low-temperature district heating systems (DHS) coupled with centralised and decentralised heat pumps. Operative conditions are defined in order to satisfy the heating needs without overloading the electric grid. The results are achieved by dynamic simulations, based on a real DHS located in southern Switzerland. At the building level, the heating needs are estimated considering real data and simultaneous energy simulations. Two DHS configurations, alternatives to the existing one, are simulated and suitable parameters for the management of the DHS are selected. The global performance of the two DHS is evaluated by KPIs also including the flexibility and the impact on the electric peak due to heat pumps. The achieved results are discussed providing suggestions for the stakeholders involved in DHS management for an optimal matching of the electric grid and thermal networks towards a reduction of the peak power. The rule-based control strategies defined allow the expected electric peak shaving and load levelling, conversely, the yearly energy consumptions are lightly increased and have to be further investigated. The outcomes demonstrate a global better performance of the ultra-low temperature DHS in terms of response to the applied control strategies and of energy savings.